Calculation the Parameters of the Filters Shaping and the Properties of Random Processes on the Output Linear Filters by Using Mathematical Modeling - Saad Z. Sekhi (Engineering and Technology Journal, 2016)
Using mathematical modeling of wireless devices and systems, where it was to provide detailed explanations about calculating parameters shaping filters features and characteristics of the operations on the exits, and the study has to solve many computational problems conventional related to the following topics: 1. Calculate the properties of random processes on the output linear filters when exposed to the input of the white Gaussian noise. 2. Calculate the parameters of the filters shaping used to simulate the random processes with giving her the spectral-correlation properties. 3. Calculation parameters of optimal detectors of radio pulses. 4. Optimal estimation of the unknown parameters of the distribution.